1998
DOI: 10.1055/s-2007-978925
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Plasma Levels of β-Endorphin in Alcoholics and Highly Trained Athletes and the Relationship to a Measure of Central Opioid Tone

Abstract: Human beta-endorphin-like immunoactivity was measured in highly trained athletes (n = 10), alcoholics in the early phase of abstinence (n=9) and normal controls (n=15) using the Nichols Allegro immunoradiometric assay. The assay was examined for cross reactivity against related peptides, beta-lipotropin and human N-acetyl beta-endorphin. Venous blood sampling was carried out in the morning at 0900 and 1100 hours in a fasting state. Using two-way analysis of variance there was a significant effect of subject gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
2

Year Published

1999
1999
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 9 publications
1
8
0
2
Order By: Relevance
“…Our data with reduced bE levels at onset and on day 14 of withdrawal are consistent with previous studies (Aguirre et al 1990;Vescovi et al 1992;Marchesi et al 1997;Inder et al 1998;Esel et al 2001). Whereas bE levels remained lowered while withdrawal symptoms subsided, the bE deficiency might be independent of the alcohol withdrawal syndrome and might contribute directly to anxiety and craving.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our data with reduced bE levels at onset and on day 14 of withdrawal are consistent with previous studies (Aguirre et al 1990;Vescovi et al 1992;Marchesi et al 1997;Inder et al 1998;Esel et al 2001). Whereas bE levels remained lowered while withdrawal symptoms subsided, the bE deficiency might be independent of the alcohol withdrawal syndrome and might contribute directly to anxiety and craving.…”
Section: Discussionsupporting
confidence: 92%
“…In rodents, alcohol exposure has been reported to increase (Cheng and Tseng 1982), decrease (Schulz et al 1980) or leave unchanged (Seizinger et al 1983) the brain and pituitary content of bE. Whereas chronic alcohol exposure has shown a rather blurred picture also in man, during alcohol withdrawal alcoholics consistently showed bE levels lower than normal (Aguirre et al 1990;Vescovi et al 1992;Inder et al 1998;Esel et al 2001). Moreover, Borg et al (1982) presented evidence that bE in the cerebrospinal fluid (CSF) and depression were associated during late alcohol withdrawal.…”
Section: Introductionmentioning
confidence: 99%
“…The functional significance of the +118A/G polymorphism has recently been demonstrated; the OPRM1 Asp40 isoform binds ␤-endorphin approximately three times more potently than the Asn40 isotype [Bond et al, 1998]. Moreover, recent studies have shown that a group of alcoholics demonstrated significantly less ␤-endorphin blood plasma immunoreactivity than unaffected controls [Inder et al, 1998] and that individuals from families with a high incidence of alcoholism exhibit diminished endogenous hypothalamic -opioid activity [Wand et al, 1998]. Such evidence suggests that the molecular mechanism for the association of the OPRM1 +118A allele with alcoholism involves hyposensitivity of OPRM1 leading to hypopotentiation of the endogenous -opioid receptor system.…”
Section: Discussionmentioning
confidence: 99%
“…Un primer análisis de los resultados confirma, una vez más, nuestros datos previos de que los alcohólicos crónicos presentan unos valores plasmáticos de β-E significativamente más bajos que los no alcohólicos (20-23) y en concordancia con otros investigadores (24).…”
Section: Discussionunclassified
“…En trabajos anteriores ya se ha comprobado que los niveles plasmáticos de β-E en los alcohólicos son más bajos que en sujetos normales, incluso tras más de 10 años de abstinencia (20)(21)(22)(23)(24), pero pocos trabajos hemos encontrado en los que se estudien estos niveles en hijos de alcohólicos, y entre éstos los resultados obtenidos son diferentes (13,25). Para intentar clarificar este aspecto hemos diseñado el presente trabajo donde estudiamos a los hijos de uno o dos progenitores alcohóli-cos y comprobamos sus niveles basales de β-E plasmática.…”
unclassified